Hooded Crows (Corvus cornix) May Be Aware of Their Own Body Size - Khvatov, Ivan A.; Smirnova, Anna A.; Samuleeva, Maria V.; Ershov, Evgeniy V.; Buinitskaya, Svetlana D.; Kharitonov, Alexander N. (Frontiers in Psychology, 2021)
Body-awareness is one of the manifestations of self-awareness, expressed in the ability of people and animals to represent their own body physical properties. Relatively little work has been devoted to this phenomenon in comparison with the studies of the ability to self-recognize in the mirror, and most studies have been conducted on mammals and human infants. Crows are known to be “clever” birds, so we investigated whether hooded crows (Corvus cornix) may be aware of their own body size. We set up an experimental design in which the crows had to pass through one of three openings to reach the bait. In the first experiment, we studied whether crows prefer a larger hole if all the three are suitable for passage, and what other factors influence their choice. In the second experiment, we assessed the ability of the crows on the first attempt to select a single passable hole out of three, even though the area of the former was smaller than that of the other two. The results of the first experiment suggest that when choosing among three passable holes, crows prefer those holes that require less effort from them, e.g. they do not need to crouch or make other additional movements. In the second experiment, crows reliably more often chose a single passable hole on the first try, despite its smaller size. We believe that these results suggest that hooded crows are aware of their own body size.